2021
DOI: 10.1001/jamaneurol.2021.1509
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Oculopharyngodistal Myopathy WithLRP12CGG Repeat Expansions Compared With Other Oculopharyngodistal Myopathy Subtypes

Abstract: and the OPDM_LRP12 Study Group IMPORTANCE Repeat expansion of CGG in LRP12 has been identified as the causative variation of oculopharyngodistal myopathy (OPDM). However, to our knowledge, the clinicopathologic features of OPDM with CGG repeat expansion in LRP12 (hereafter referred to as OPDM_LRP12) remain unknown.OBJECTIVE To identify and characterize the clinicopathologic features of patients with OPDM_LRP12. DESIGN, SETTING, AND PARTICIPANTSThis case series included 208 patients with a clinical or clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 43 publications
3
86
1
Order By: Relevance
“…Serum creatine kinase levels are usually normal or mildly increased in individuals with OPDM, and skeletal muscles shows moderate fibrosis and small angular fibers. Besides these non-specific myopathic changes, OPDM histopathology is characterized by the presence of cytoplasmic rimmed vacuoles (RVs) and typical eosinophilic nuclear inclusions (NIs), which are both p62-and ubiquitin-positive ( Zhao et al, 2015 ; Deng et al, 2020 ; Saito et al, 2020 ; Kumutpongpanich et al, 2021 ; Matsubara et al, 2021 ; Xi et al, 2021 ). Of interest, these intranuclear inclusions are also observed in skin sections of individuals with OPDM cases ( Ogasawara et al, 2021 ), and are reminiscent of the typical inclusions observed in FXTAS and NIID.…”
Section: Oculopharyngodistal Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum creatine kinase levels are usually normal or mildly increased in individuals with OPDM, and skeletal muscles shows moderate fibrosis and small angular fibers. Besides these non-specific myopathic changes, OPDM histopathology is characterized by the presence of cytoplasmic rimmed vacuoles (RVs) and typical eosinophilic nuclear inclusions (NIs), which are both p62-and ubiquitin-positive ( Zhao et al, 2015 ; Deng et al, 2020 ; Saito et al, 2020 ; Kumutpongpanich et al, 2021 ; Matsubara et al, 2021 ; Xi et al, 2021 ). Of interest, these intranuclear inclusions are also observed in skin sections of individuals with OPDM cases ( Ogasawara et al, 2021 ), and are reminiscent of the typical inclusions observed in FXTAS and NIID.…”
Section: Oculopharyngodistal Myopathiesmentioning
confidence: 99%
“…Of interest, these intranuclear inclusions are also observed in skin sections of individuals with OPDM cases ( Ogasawara et al, 2021 ), and are reminiscent of the typical inclusions observed in FXTAS and NIID. Importantly, the mutations causing OPDM were recently identified as similar expansions of ∼70 to 200–300 CGG repeats located within the 5′UTR of two different genes, LRP12 and GIPC1 ( Ishiura et al, 2019 ; Deng et al, 2020 ; Kumutpongpanich et al, 2021 ; Xi et al, 2021 ). Furthermore, an expansion of CGG repeats in the 5′UTR of the NOTCH2NLC gene was identified in OPDM cases with variable neurological manifestations ( Ogasawara et al, 2020 ; Yu et al, 2021 ), and an expansion of CGG repeats within the 5′UTR of the RILPL1 gene was recently reported in medRxiv in affected individuals of a large Chinese family with OPDM ( Yang et al, 2021 ).…”
Section: Oculopharyngodistal Myopathiesmentioning
confidence: 99%
“…Abundancy of polymorphic CGG repeats in the human genome suggest a broad involvement in neurological diseases 15 . Large GGC expansions are strictly linked to neurological disorders of predominant neurocognitive impairment, such as fragile X-associated tremor and ataxia syndrome, NIID, and oculopharyngeal muscular dystrophy 16 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In a global perspective, abundancy of polymorphic CGG repeats in the human genome suggest a broad involvement in neurological diseases 12 . Large GGC expansions are strictly linked to neurological disorders of predominant neurocognitive impairment, such as fragile X-associated tremor and ataxia syndrome, NIID, and oculopharyngeal muscular dystrophy [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%